Manuskrip Kampar - Devi Fauziyah Ma'rifat (Jurnal Mengkaji Indonesia, 2022)
Abstract: A handwritten text is called a manuscript. It is considered a cultural heritage from a society’s history in the past. A manuscript contains various expressions of emotions and thoughts of culture in the past and has historical elements. Manuscripts become objects of research in various fields of science, including philology, history, archeology, codicology, and paleography. Each ancient manuscript holds cultural values, but its form does not appear explicitly, so gradual and careful research is needed to identify them. Purpose: Readers can understand the text and know the moral message it implies. Design/Methodology/Approach: Through contextual analysis, readers can recognize and understand the concept of cultural values. Findings: Readers can understand the moral message it carries. Originality/Value: Produces a critical edition that readers can understand.